2011
DOI: 10.1038/nrneurol.2010.198
|View full text |Cite
|
Sign up to set email alerts
|

Therapies for multiple sclerosis: considerations in the pediatric patient

Abstract: Current and emerging therapies for multiple sclerosis (MS) offer promise for improved disease control and long-term clinical outcome. To date, these therapies have been evaluated solely in the context of adult MS. However, onset of MS in children is being increasingly recognized, and recent studies have identified a significant impact of MS onset during childhood on cognitive and physical functioning. Optimization of pediatric MS care requires that promising new therapies be made available to children and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 155 publications
(139 reference statements)
1
25
0
3
Order By: Relevance
“…26,27 Assuming that first-line disease-modifying therapies in children should provide a reduction in relapses similar to the 30%-40% observed in adults, a treatment goal would be to initially achieve an annualized relapse rate (ARR) lower than 0.6 relapses per year (or roughly 1 relapse over the first 2 years of disease) and #0.35 between years 2-5 post disease onset. 26,27 Treatment benefit in adult MS trials often includes absence of sustained Expanded Disability Status Scale (EDSS) increase. This metric is less appropriate in pediatric-onset MS as EDSS rarely worsens during the first 10 years following disease onset.…”
Section: Definition Of No Evidence Of Diseasementioning
confidence: 99%
“…26,27 Assuming that first-line disease-modifying therapies in children should provide a reduction in relapses similar to the 30%-40% observed in adults, a treatment goal would be to initially achieve an annualized relapse rate (ARR) lower than 0.6 relapses per year (or roughly 1 relapse over the first 2 years of disease) and #0.35 between years 2-5 post disease onset. 26,27 Treatment benefit in adult MS trials often includes absence of sustained Expanded Disability Status Scale (EDSS) increase. This metric is less appropriate in pediatric-onset MS as EDSS rarely worsens during the first 10 years following disease onset.…”
Section: Definition Of No Evidence Of Diseasementioning
confidence: 99%
“…10 This definition might be conservative with regards to relapse activity, and another review has suggested that an annual relapse rate .0.6 in the first 2 years of disease or .0.35 in years 2-5, or $3 new lesions in the first year and .2 lesions in years 2 and 3, would indicate inadequate treatment response. 11 None of these definitions has formally been applied to pediatric MS cohorts, and the percentage of children with inadequate treatment response is therefore unknown. A retrospective analysis of 258 treated pediatric patients with MS revealed that 28% were considered by their health care practitioners to have refractory disease on their first therapy (mainly IFN and GA), and were therefore switched to a second therapy after a mean of 1.3 years.…”
Section: Conceptual Approaches To Treating Children With Msmentioning
confidence: 99%
“…All first-and second-line MS therapies used in children and adolescents are off-label since immunomodulatory therapies currently approved for adults with MS have not been formally evaluated by clinical trials in children [Tenembaum, 2010;Kuntz et al 2010;Ghezzi, 2010;Banwell et al 2011]. However, consensus recommendations regarding the use of existing first-and second-line therapies, as well as the evaluation of new therapies in paediatric patients with MS, have recently been published by the International Pediatric Multiple Sclerosis Study Group (IPMSSG) [Chitnis et al 2012].…”
Section: Introductionmentioning
confidence: 99%